سمة الغرور لدى الطلبة المتفوقين دراسة مقارنة (Journal of the College of Basic Education, 2024)
Vanity is one of the traits that form from the beginning of an individual’s formation during the early childhood stage. It strengthens when it receives repeated reinforcement and reward from parents until it becomes part of the components of the personality as a clear manifestation in the later stages of life in adolescence and adulthood, and its behaviors are of a selfish nature, and the trait of vanity comes. An effective response is the person’s relationship with himself, the ideas he forms about it, and the degree of his adherence to them and his defense of them, including the intervention of other elements such as self-esteem and maintaining dignity and moral character.For the personality and position that a person places for himselfThe current research aims:1- Identifying the trait of vanity among outstanding students2- The significance of the statistical differences between males and females.